2011
DOI: 10.1371/journal.pone.0018002
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles of Cdc42 in Thymopoiesis and Effector and Memory T Cell Differentiation

Abstract: Cdc42 of the Rho GTPase family has been implicated in cell actin organization, proliferation, survival, and migration but its physiological role is likely cell-type specific. By a T cell-specific deletion of Cdc42 in mouse, we have recently shown that Cdc42 maintains naïve T cell homeostasis through promoting cell survival and suppressing T cell activation. Here we have further investigated the involvement of Cdc42 in multiple stages of T cell differentiation. We found that in Cdc42−/− thymus, positive selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 48 publications
1
59
0
Order By: Relevance
“…The decreased numbers of SP thymocytes may not only result from defective β-selection, but also from impaired positive selection and/or lineage commitment. To examine positive selection in RhoA −/− mice, we analyzed DP, CD4 + SP and CD8 + SP thymocytes for the surface expression of CD69, upregulation of which is a critical marker of successful positive selection (34). We found that RhoA −/− mice had more CD69 hi CD4 + CD8 + , but less CD69 hi CD4 + and CD69 hi CD8 + , thymocytes than the WT control mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decreased numbers of SP thymocytes may not only result from defective β-selection, but also from impaired positive selection and/or lineage commitment. To examine positive selection in RhoA −/− mice, we analyzed DP, CD4 + SP and CD8 + SP thymocytes for the surface expression of CD69, upregulation of which is a critical marker of successful positive selection (34). We found that RhoA −/− mice had more CD69 hi CD4 + CD8 + , but less CD69 hi CD4 + and CD69 hi CD8 + , thymocytes than the WT control mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4A). To determine at which specific point DP thymocyte development was blocked in RhoA −/− mice, we analyzed the expression of TCRβ together with CD69 in total thymocytes (1, 34), by FACS. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, SLIT/ROBO signaling can influence the expression of Rac1 and CDC42 [33]. Rac1 plays a crucial role in T cell development [34] while CDC42 is essential for memory T cell growth and differentiation [35,36]. Therefore, SLIT/ROBO signaling could contribute to adaptive immunity through Rac1 or/and CDC42.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] To achieve a T-cell-restricted deletion, we crossed conditional Cdc42 fl/fl or Rac1 fl/fl mice with CD4Cre mice that express the Cre recombinase in both CD4 and CD8 T cells under the control of the CD4 minimal promoter. 20 By using this approach, we aimed at deleting Cdc42 or Rac1 simultaneously with the induction of NPM-ALK expression, because NPM-ALK expression is under the control of the same CD4 promoter.…”
Section: Rac1 and Cdc42 Possess Nonredundant Roles In Npm-alk-mediatementioning
confidence: 99%